GPS and GSM based vehicle tracker - S. M. A., Motakabber; AHM, Zahirul Alam; Maurice Francis, Mohamed Reda; Fawwaz Wafa, Syed Ahmad (AlamBiblio Publishers, 2022)
Nowadays, electronic wireless vehicle tracking is becoming essential for preventing car theft and emergency services in vehicle accidents. There are three types of vehicle tracking systems in the market. Each has its advantages and disadvantages. Based on the working principle, these trackers are classified as cellular phone-based trackers, wireless passive trackers, and real-time satellite trackers. This paper has discussed designing and developing a vehicle tracking system using an Arduino microcontroller, GSM, and GPS modules. The proposed design is a different approach to these vehicle tracking systems. The function of the tracker is done in three steps; first, it connects the hardware components and tests the connectivity; when the secure connectivity is confirmed, it executes the write command for the connected GSM and GPS modules. Finally, it tracks the target vehicle, collects the GPS coordinates, and processes the data using the software. The proposed design has been verified by MATLAB simulation, and the results obtained are satisfactory for both simulation and practical examination